¿Cómo traducir el lunfardo al alemán? El reto de la variación lingüística en la traducción audiovisual - Gugenberger, Eva (Linguistik Online, 2017)
This article focuses on the problems arising from non-standard varieties in the translation of audiovisual texts using the example Lunfardo. This special repertoire of words, which originated in the late 19th century in the lower classes in Buenos Aires, has become a commonly used and characteristic part of colloquial Rioplatense Spanish. Taking the example Okupas, an Argentine TV series for young people, and guided by the priority function that the use of Lunfardo has in the series, this study intends to identify an appropriate style of speech for dubbing into German. Based on a selected dialogue, some results are presented that were developed in class together with students of translation. The objective of the analysis is to demonstrate that it is possible to find more creative and adequate solutions to go further than the usual practice to level diasystematic characteristics when translating into standard German.